Re-Use of Caco-2 Monolayers in Permeability Assays-Validation Regarding Cell Monolayer Integrity - Cristiana L. Pires; Catarina Praça; Patrícia A. T. Martins; Ana L. M. Batista de Carvalho; Lino Ferreira; Maria Paula M. Marques; Maria João Moreno (MDPI AG, 2021)
Caco-2 monolayers are a common in vitro model used to evaluate human intestinal absorption. The reference protocol requires 21 days post-seeding to establish a stable and confluent cell monolayer, which is used in a single permeability assay during the period of monolayer stability (up to day 30). In this work, we characterize variations in the tightness of the cell monolayer over the stable time interval and evaluate the conditions required for their re-use in permeability assays. The monolayer integrity was assessed through TEER measurements and permeability of the paracellular marker Lucifer Yellow (LY), complemented with nuclei and ZO-1 staining for morphological studies and the presence of tight junctions. Over 150 permeability assays were performed, which showed that manipulation of the cell monolayer in the permeability assay may contribute significantly to the flux of LY, leading to Papp values that are dependent on the sampling duration. The assay also leads to a small decrease in the cell monolayer TEER, which is fully recovered when cell monolayers are incubated with culture media for two full days. When this procedure is followed, the cell monolayers may be used for permeability assays on days 22, 25, and 28, triplicating the throughput of this important assay.